Survival and growth of siganid (Siganus guttatus) in floating net cages fed with commercial formulated feed and filamentous green alga (Chaetomorpha linum) - Toledo, Ceferino Fernandez (Iloilo Graduate Faculty, University of the Philippines System, 1990)
Four experimental feeds namely : commercial formulated feed (CFF) containing 25% crude protein (Treatment I), CFF containing 30% crude protein (Treatment 2), combination of 50% CFF containing 30% crude protein and 50% filamentous green algae (lumut) (Treatment 3) and "lumut" only (Tretament 4) were tested to determine their effects on the survival and growth of Siganus guttatus reared in floating net cages in seawater at a stocking density of 50 fish/m3 for 122 daysResults indicated that commercial formulated feeds had significantly better effects on growth and production of S. guttatus compared with the combination of 50% CFF and 50% "lumut" and the "lumut" only. The highest mean growth of 77.7 g/fish and production 0f 4.18 kf/m3 cage obtained in Treatment 2 did not differ significantly from the growth of70.1 g/fish and production of 3.86 kg/m3 in Treatment 1. On the other hand, the growth of 44.9 g/fish and a production of 2.56 kg/m3 obtained in Treatment 3 was notsignificantly different from the lowest growth of 40.8 g/fish and production of 2.26 kg/m3 in Treatment 4. The mean rate of survival ranged from 89-96% with no significant differencesamong the four treatments. Treatment 2, 1 and 3 in this order had a mean conversion values of 2.4, 2.5 and 3.4 respectively which were not significantly different from each other buthighly different from Treatment 4 (18.1). The commercial formulated feeds with 25% and 30% crude protein (CP) appeared to be economically feasible as feed for net cage culture of S.guttatus. A net income of P113.25/m3 cage and a benefit-cost ratio of 1.47 were obtained from fish fed with the CFF containing 30% CP, while only Php 75.50 and 1.32 were obtained from fish fed with the CFF containing 25% CP.
Thesis (M. S. Fisheries-Aquaculture) - U. P. System, May 1990.
Keywords: Siganid; Siganus guttatus; Algae; Chaetomorpha linum; Net cages; Feeds and feeding